Effect of Organizational Culture, Pay Satisfaction, Job Satisfaction on Nurse Intention to Leave at Private Hospital Type D in Bantul - Dimas Sigit Widodo; Nur Hidayah; Siti Dyah Handayani (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2021)
The study aims to identify the effect of organizational culture, pay satisfaction, job satisfaction on nurse intention to leave at Private Hospital Type D in Bantul. This study used a quantitative approach with a crossectional design. Collecting data using an instrument in the form of a questionnaire. This study uses SEM method analysis techniques using AMOS software. The results showed that there is a positive effect of organizational culture (c.r. 5,048, p 0,000) and nurse pay satisfaction (c.r. 3,713, p 0,000) on nurse job satisfaction. There is a negative effect of organizational culture (c.r. -3,123, p 0,002) and nurse pay satisfaction (c.r. -2,336, p 0,019) on the nurse intention to leave. There is no effect of nurse job satisfaction (c.r. -0,916, p 0,36) to nurse intention to leave.